Aeon as an Expression of Metaphysics of Transcendence and Metaphysics of Immanence in John Damascene - Petridou, Lydia; Terezis, Christos (Vox Patrum, 2020)
In this study the concept of ‘aeon’ in John Damascene is discussed. More specifically, relying on his treatise under the title An exact Exposition of the Orthodox Faith, the relation between aeon and the created world, as well as the resulted from it combination of Cosmology with Eschatology, are first of all investigated. Subsequently, the relation between aeon and the Holy Trinity, taking into account all the ways in which it is manifested, as well as the combination of Henology with Eschatology, are approached. Throughout the entire reasoning, it arises that the Christian thinker utilizes the Words, that is, the divinely inspired texts, as an objective proof for the Christian validity of his arguments. The most important conclusion drawn is that the term “aeon” has many meanings and each one of them is formulated according to the metaphysical or natural ontological plane to which they refer.